Mitochondrial Alterations, Oxidative Stress, and Therapeutic Implications in Alzheimer’s Disease: A Narrative Review - Erica Spina; Riccardo Rocco Ferrari; Elisa Pellegrini; Mauro Colombo; Tino Emanuele Poloni; Antonio Guaita; Annalisa Davin (Cells)
The relationship between aging, mitochondrial dysfunction, neurodegeneration, and the onset of Alzheimer’s disease (AD) is a complex area of study. Aging is the primary risk factor for AD, and it is associated with a decline in mitochondrial function. This mitochondrial dysfunction is believed to contribute to the neurodegenerative processes observed in AD. Neurodegeneration in AD is characterized by the progressive loss of synapses and neurons, particularly in regions of the brain involved in memory and cognition. It is hypothesized that mitochondrial dysfunction plays a pivotal role by disrupting cellular energy metabolism and increasing the production of reactive oxygen species (ROS), which can damage cellular components and exacerbate neuronal loss. Despite extensive research, the precise molecular pathways linking mitochondrial dysfunction to AD pathology are not fully understood. Various hypotheses have been proposed, including the mitochondrial cascade hypothesis, which suggests that mitochondrial dysfunction is an early event in AD pathogenesis that triggers a cascade of cellular events leading to neurodegeneration. With this narrative review, we aim to summarize some specific issues in the literature on mitochondria and their involvement in AD onset, with a focus on the development of therapeutical strategies targeting the mitochondria environment and their potential application for the treatment of AD itself.